2008
DOI: 10.3727/096504008784523667
|View full text |Cite
|
Sign up to set email alerts
|

CCR5-Δ32 Polymorphism and Susceptibility to Cervical Cancer: Association With Early Stage of Cervical Cancer

Abstract: Inflammation plays a major role in the pathogenesis of cervical cancer. Chemokines are involved in inflammation, cancer, and infectious diseases. Therefore, we evaluated the association of the chemokine receptor gene polymorphism CCR5 Delta32 with risk of cervical cancer. A total of 150 histopathologically confirmed patients with cervical cancer and 162 age and ethnically matched cervical cytology negative healthy controls were genotyped for CCR5 Delta32 polymorphisms using PCR. Association of CCR5 Delta32 gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…Genetic factors are another feature affecting CCR5 expression. 9 For instance, the ∆32 mutation in the unique CCR5 exon, which leads to a decreased expression of CCR5, [8][9][10] was evaluated in these patients. The results of this study demonstrated that none of the OBI patients presents CCR5-∆32 mutations, hence, a decrease of CCR5 on CD8 + T cells may not be related to the ∆32 mutations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic factors are another feature affecting CCR5 expression. 9 For instance, the ∆32 mutation in the unique CCR5 exon, which leads to a decreased expression of CCR5, [8][9][10] was evaluated in these patients. The results of this study demonstrated that none of the OBI patients presents CCR5-∆32 mutations, hence, a decrease of CCR5 on CD8 + T cells may not be related to the ∆32 mutations.…”
Section: Discussionmentioning
confidence: 99%
“…7 The mutation in the first exon of CCR5, known as ∆32 mutation (deletion of 32 nucleotides in the exon 1), was reported to cause decreased expression and dysfunction of the receptor. [8][9][10] This mutation is polymorphic in different populations, 2 and because we intended to analyze the CCR5 expression on CD8 + T cells in OBI patients, the present investigation was designed to study this polymorphism in Iranian patients. The main immune cells involved in immunity against HBV are CD8 + T cells.…”
mentioning
confidence: 99%
“…CCR5 is implicated in the immunological response to a variety of pathogens [37] and evidence indicates that, despite having an apparently normal phenotype, individuals homozygous for the CCR5-∆32 deletion who lack functional CCR5 might have an increased susceptibility to disease following West Nile virus infection [38] or tick-borne encephalitis [39]. In addition, conflicting reports of associations between CCR5-∆32 and various malignancies [40][41][42][43][44][45] combined with a cluster of lymphomas observed in the Phase IIb ACTG 5211 study of vicriviroc have also caused concern regarding the potential for an increase in malignancies. Data demonstrating that CCR5-∆32 mice have an increased susceptibility to concanavalin A-induced hepatitis [46,47], when considered together with the severe idiosyncratic hepatotoxicity observed during aplaviroc development, have also raised concerns that hepatotoxicity could be a class effect.…”
Section: Ccr5 Antagonist Safety and Tolerabilitymentioning
confidence: 99%
“…Indeed, the only recorded case of HIV cure occurred after a patient received a hematopoietic stem cell transplant from a donor who was homozygous for the inactivating CCR5del32 allele 5 . Individuals with this allelic variant, however, have increased susceptibility to some viral infections 6 , cancers 7,8 , and other diseases 9 , suggesting that gene therapy approaches will benefit from the identification of other non-essential host genes required for HIV infection.…”
Section: Introductionmentioning
confidence: 99%